MECHANICAL PROPERTIES OF STARCH COMPOSITE REINFORCED BY PINEAPPLE LEAF FIBER (PLF) FROM JOSAPINE CULTIVAR - Selamat, Mohd Zulkefli; Sivakumar, Dhar Malingam; Azma, Putra; Ahadlin, Mohd Daud; Yuhazri, Yaakob (Asian Research Publishing Network (ARPN), 2016)
Nowadays, there is an increase in research about renewable natural fiber as an alternative solutions in replacing synthetic fibers such as glass fiber as reinforced composites materials that are non – biodegradable and non – ecofriendly to the system. Natural fibers are also known for its low cost production yet have excellent mechanical properties and is environmental friendly. One of the natural fiber resource is pineapple leaf fiber (PLF) which is planted widely in Malaysia. From current research, PLF contains high cellulose and exhibits good mechanical properties especially from Josapine family. In this study, the PLF from Josapine is used as reinforced materials and starch (SH) is used as the binder. Additionally, the effects of PLF loading and PLF fiber length on the mechanical properties of PLF/SH composites is also analyzed. Compositions ratio of PLF/SH composites is fixed at 50/50, 60/40 and 70/30. The lengths of the fiber are fixed to 2 cm, 4 cm and 6 cm. Before the fabrication, PLF has underwent alkaline treatment to increase the strength of fiber. All nine samples has underwent four different tests to determine the mechanical properties which are tensile test, hardness, density and microstructure analysis. PLF loading of 70% with 6 cm in length shows the higher values of tensile stress, density and hardness which are 14.53 MPa, 33.63 and 1.20 g/cm3 respectively.